Borrowing Company Names in the Practice of Procurement of Goods and Services in Indonesia - Trisulo Trisulo (Universitas Pelita Harapan, 2022)
Normatively, regulations regarding the procurement of goods and services contribute significantly to the efficiency of state spending and the national economy. But in practice, there are still deviations that have the potential to violate the law. This article examines the borrowing of company names in the practice of procurement of government goods and services from the perspective of the applicable law, and the perspective of Dignified Justice. The research methodology used is normative legal research with a literature study using primary, secondary, and tertiary legal materials. As a theoretical basis, this research uses the Theory of Dignified Justice. This article shows that borrowing company names in the practice of procuring government goods and services are contrary to applicable legal norms, and can be a criminal element for providing false or fraudulent information. Existing regulations are not able to touch the practice of borrowing company names in practice. From the perspective of Dignified Justice, it is also identified as contrary to morals, nor does it meet the criteria of good faith in the agreement. To guarantee legal certainty, the practice of borrowing company names must be strictly prohibited by law, but it needs to be done without conflicting with the economic objectives referred to by the constitution.